Deagglomeration testing of airborne nanoparticle agglomerates: Stability analysis under varied aerodynamic shear and relative humidity conditions. Issue 11 (1st November 2016) - Ding, Yaobo; Stahlmecke, Burkhard; Kaminski, Heinz; Jiang, Yunhong; Kuhlbusch, Thomas A. J.; Riediker, Michael
ABSTRACT: Occupational exposure to nanomaterial aerosols poses potential health risks to workers at nanotechnology workplaces. Understanding the mechanical stability of airborne nanoparticle agglomerates under varied mechanical forces and environmental conditions is important for estimating their emission potential and the released particle size distributions, which in consequence alters their transport and human uptake probability. In this study, two aerosolization and deagglomeration systems were used to investigate the potential for deagglomeration of nanopowder aerosols with different surface hydrophilicity under a range of shear forces and relative humidity conditions. Critical orifices were employed to subject airborne agglomerates to the shear forces induced by a pressure drop. Increasing applied pressure drop was found to be associated with decreased mean particle size and increased particle number concentrations. Rising humidity decreased the deagglomeration tendency as expressed by larger modal particle sizes and lower number concentrations compared to dry conditions. Hydrophilic aerosols exhibited higher sensitivities to changes in humidity than hydrophobic particles. However, the test systems themselves also differed in generated particle number concentrations and size distributions, which in turn altered the responses of created aerosols to humidity changes. The results of the present study clearly demonstrate that (a) humidity control is essential for dustiness and deagglomeration testing, (b) that (industrial) deagglomeration, for example, for preparation of aerosol suspensions, can be manipulated by subjecting airborne particles to external energies, and (c) that the humidity of workplace air may be relevant when assessing occupational exposure to nanomaterial aerosols. Copyright © 2016 American Association for Aerosol Research